Personal Data Protection in the Digital Era: A Maqasid al-Shariah Perspective on Contemporary Legal Challenges - Kukuh Pandu Wicaksana; Tahegga Primananda Alfath; Heru Kuswanto (JURNAL ILMU SYARIAH, 2026)
Personal data has become one of the most valuable assets in the digital era, yet its extensive collection and processing by digital platforms, corporations, and government institutions have created significant risks of misuse, unauthorized disclosure, and violation of individual privacy. While Indonesia has responded through Law Number 27 of 2022 concerning Personal Data Protection, positive law alone provides limited ethical grounding for evaluating why such protection matters and how far it should extend, particularly in the face of emerging challenges such as algorithmic profiling and automated decision-making. This study examines personal data protection through the lens of Maqasid al-Shariah, the objectives of Islamic law, to identify the extent to which Islamic legal reasoning can complement and, in certain respects, extend the normative foundations of positive data protection law. Using normative legal research with statutory, conceptual, and comparative approaches, this study analyzes primary legal materials, including Qur'anic verses, authentic hadith, and Indonesian data protection legislation, alongside secondary materials drawn from classical and contemporary Maqasid al-Shariah scholarship. The analysis employs qualitative content analysis, categorizing findings according to the dimensions of hifzh al-din, al-nafs, al-'aql, al-nasl, al-mal, and the contemporary extension of hifzh al-'irdh. The findings show that core principles of Law Number 27 of 2022, namely lawfulness, transparency, purpose limitation, and accountability, are substantively consistent with the Islamic principles of taradhi (mutual consent), amanah (trustworthiness), 'adl (justice), and dar' al-mafasid (prevention of harm). However, the analysis also identifies areas where Maqasid al-Shariah offers a broader ethical horizon than current positive regulation, particularly regarding the algorithmic manipulation of human reasoning (hifzh al-'aql) and the moral, rather than merely administrative, character of data trusteeship. This study concludes that harmonizing Islamic legal objectives with positive data protection law can produce a more comprehensive, ethically grounded framework for digital governance in Muslim-majority societies such as Indonesia. Keywords: personal data protection; Maqasid al-Shariah; digital privacy; Islamic law; Law Number 27 of 2022.